A Survey of Faculty Advisers at Student-Run Agencies: Can Organizational Theory Help to Guide Future Research?. (May 2021) - Borgognoni, Brooke; LeBlanc Wicks, Jan
This survey of faculty advisers examined major variables and findings of past research on student-run agencies using organizational theory. Larger agencies appeared to offer training in more formalized business procedures among a more diverse client base, found in previous research to be helpful to student-run agency graduates now on the job. Hopefully, results will help future researchers identify which factors may best facilitate specific student performance outcomes at agencies of all types and sizes.